Properties of gypsum particleboard with added mineral dolomite - Umit Yalçin, Omer; İhsan Kaya, Ali (Maderas. Ciencia y Tecnología, 2022)
Red pine (Pinus brutia) wood particles and dolomite mineral were used in varying proportions to form mineral-added gypsum particleboards. Mechanical, physical, and chemical properties of the boards were tested. The increasing mineral content was found to improve the water absorption properties but the increased amount of gypsum in the mixture negatively affected the thickness swelling and water absorption properties. The usage of dolomite mineral in the board composition increased the internal bond properties and higher than the standard of 0,28 MPa. However, all types of boards had modulus of elastic, modulus of rupture and thermal conductivity results values below the standards. Moreover, the thermal conductivity values decreased in all board types because of the reduction of the mineral dolomite. Thermal gravimetric analysis, Fourier transform infrared spectrometry tests were applied to examine the thermal and flame retardancy properties of inorganic materials, wood-gypsum composites, which are used at different rates for synergistic effect. The gypsum and dolomite amount affected the thermal variation, whereas the increment in the weight of the wood particles also increased the thermal degradation. It was determined that stresses at 850-980 cm-1 reveal Ca-O and Mg-O, reveal at 881cm-1 C-OH, weak vibration at 1619 cm-1 and a strong bond structure in the 1445-950-882 cm-1 bands. These bands express the characteristic presence of the CaO and MgO belonging to dolomite. The study demonstrated the feasibility of producing mineral-based gypsum board products using wood chips.